Prevalence and Associated Factors of Work-Related Injury Among Municipal Solid Waste Collectors in Hawassa City, Southern Ethiopia: A Cross-Sectional Study - Amanuel Ejeso; Yohannes Seifu Berego; Mahmud Ahmednur (SAGE Publishing, 2024)
Introduction: Municipal solid waste collectors are at risk of experiencing work-related health problems due to the waste they handle and the physical effort they put in. Work-related injuries among domestic waste collectors have been the subject of scant research in developing nations. Therefore, it is necessary to describe work-related injuries in these subpopulation groups. Objective: This study aimed to determine the prevalence and associated factors of work-related injury among municipal solid waste collectors in Hawassa city, Southern Ethiopia. Methodology: A cross-sectional study was conducted from January 11 to 30, 2022, with all the registered municipal solid waste collectors (411). Three diploma environmental health professionals assisted in collecting data using a pretested structured interviewer-administered questionnaire; 1 Bachelor of Science environmental health professional served as a supervisor. Statistical Package for the Social Sciences (SPSS) version 20.0 was used to enter, clean, code, and analyze the data. Associations between independent and dependent variables were assessed, and the strength of the associations was presented by using Adjusted Odds Ratio (AOR) and 95% confidence intervals (CI). According to the bivariable analysis, all independent variables associated with a P -value <.25 were entered into a multivariable logistic regression model. Variables in the multivariable regression analysis were considered significant if their P -value was less than 0.05. Results: In this study, the prevalence of work-related injuries within the last 30 days was 12.9% (95% CI: 9.5, 16.3), while the prevalence over the last 12 months was 59.4% (95% CI: 54.7, 64.0). After adjusting for possible confounding factors, age 18 to 24 years [AOR = 1.72;95% CI: (1.07, 2.76)], lack of personal protective equipment (PPE) utilization [AOR = 2.30; 95% CI: (1.44, 3.68)], chewing khat (yes) [AOR = 2.32;95% CI: (1.32, 4.08)], drinking alcohol (yes) [AOR = 1.80; 95% CI: (1.003, 3.24)] and job dissatisfaction [AOR = 2.26, 95% CI: (1.44, 3.54)] were shown to be significantly associated with work-related injury. Conclusion: The prevalence of work-related injuries was high. Age 18 to 24 years, chewing khat, drinking alcohol, lack of PPE utilization, and job dissatisfaction were significantly associated with work-related injury. Based on the findings of this study, we suggest that addressing these risk factors could help to reduce work-related injuries.